The effects of infant behavioural sleep interventions on maternal sleep and mood, and infant sleep: A randomised controlled trial. (6th April 2021) - Rouzafzoon, Mozhgan; Farnam, Farnaz; Khakbazan, Zohre
Summary: Infant sleep problems are one of the first challenges for parents, negatively influencing infants and mothers. The present study examined the effects of preventive behavioural sleep intervention (BSI) on infant sleep patterns, maternal sleep quality, and depression. A clinical randomised multicentre controlled trial was conducted involving 82 mothers and their infants aged 2–4 months in Iran from August 2018 to April 2019. The intervention group received BSI, which included one individual 90‐min class session, booklet, voice messages, and follow‐up calls; while the control group received training on general infant safety. Details of infant sleep, maternal sleep quality, and postnatal depression were measured through the sleep diary, Pittsburgh Sleep Quality Index, and Edinburgh Postnatal Depression Scale, respectively, before and at 8 weeks after the training. In the intervention group, both the mean infant "night‐time sleep period" and infant "longest self‐regulated sleep period" were 81 min longer than the controls ( p  < .001). With an improvement of 160 min, the mean infant bedtime was decreased to 22:20 hours in the intervention group, substantially earlier than the controls (00:30 hours). The mean infant "night‐time awakenings with signals" did not significantly change (2.6‐ and 2.5‐times in the intervention and control groups, respectively). The intervention led to a significant improvement in maternal sleep quality and depression ( p  < .05). The present study acknowledges the positive effects of an early preventive infant BSI on infant sleep, maternal mood, and maternal sleep. Our present results also imply the importance of considering sleep patterns differences and cultural‐based intervention's design.